The Influence of Price Discount, Bonus Pack, Brand Image on Impulse Buying of Cuddleme Products in Yogyakarta - Gunawan, Hamzah; Pratiwi, Intan (Formosa Journal of Science and Technology, 2024)
This study aims to analyze the effect of price discounts, bonus packs, and brand image on impulse buying behavior for CuddleMe products in Yogyakarta. The sample of this study consists of 40 respondents who have purchased CuddleMe products at least once within the last year or in the year 2023, and respondents who made purchases of CuddleMe products in the Yogyakarta area. The data collection technique used in this research is a survey method with a questionnaire as the research instrument. The data was processed using regression linear, t test, F test. The results of this research prove that: (1) Price Discount does not significantly influence impulse buying behavior for CuddleMe products in Yogyakarta, (2) Bonus Pack does not significantly influence impulse buying behavior for CuddleMe products in Yogyakarta, (3) Brand Image influences impulse buying behavior for CuddleMe products in Yogyakarta, (4) Price Discount, Bonus Pack, and Brand Image simultaneously have a significant influence on impulse buying behavior for CuddleMe products in Yogyakarta. These findings imply that further researchers should explore the impulse buying behavior influenced by various factors. The findings of this research have implications for CuddleMe product manufacturers to formulate strategies for customers who have purchased their products to exhibit impulse buying behavior.